A subspace approach to high‐resolution spectroscopic imaging. Issue 4 (4th February 2014) - Lam, Fan; Liang, Zhi‐Pei
<x xml:space="preserve">Abstract</x> Purpose To accelerate spectroscopic imaging using sparse sampling of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0ftwwp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(k, t)</alternatives>‐space and subspace (or low‐rank) modeling to enable high‐resolution metabolic imaging with good signal‐to‐noise ratio. Methods The proposed method, called SPectroscopic Imaging by exploiting spatiospectral CorrElation, exploits a unique property known as partial separability of spectroscopic signals. This property indicates that high‐dimensional spectroscopic signals reside in a very low‐dimensional subspace and enables special data acquisition and image reconstruction strategies to be used to obtain high‐resolution spatiospectral distributions with good signal‐to‐noise ratio. More specifically, a hybrid chemical shift imaging/echo‐planar spectroscopic imaging pulse sequence is proposed for sparse sampling of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t0ftwx7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(k, t)</alternatives>‐space, and a low‐rank model‐based algorithm is proposed for subspace estimation and image reconstruction from sparse data with the capability to incorporate prior information and field inhomogeneity correction. Results The performance of the proposed method has been evaluated using both computer simulations and phantom studies, which produced very encouraging results. For two‐dimensional spectroscopic imaging experiments on a metabolite phantom, a factor of 10 acceleration was achieved with a minimal loss in signal‐to‐noise ratio compared to the long chemical shift imaging experiments and with a significant gain in signal‐to‐noise ratio compared to the accelerated echo‐planar spectroscopic imaging experiments. Conclusion The proposed method, SPectroscopic Imaging by exploiting spatiospectral CorrElation, is able to significantly accelerate spectroscopic imaging experiments, making high‐resolution metabolic imaging possible. Magn Reson Med 71:1349–1357, 2014. © 2014 Wiley Periodicals, Inc.